STUDIES ON THE USE OF WOOD ON FRAME IN TANJUNG BAKAU’S VILLAGE RANGSANG’S SUB-DISTRICT REGENCY OF KEPULAUAN MERANTI PROVINCE OF RIAU - Tos arianto; Syaifuddin '; Ronald M Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on June 2014 at Tanjung Bakau’s Village Rangsang’s Sub-district Regency of Kepulauan Meranti Province of Riau. The methods used is survey method. There are three steps to finish the research. The first step is preparation and survey. The second step is data retrieval and the third step is processing and analysis of data. The purpose of this research was to analyze the process manufacture of the frame and wood in the ship. Therefore the level of efficiency on used wood as was calculated to obtain its percentase. The wood type that used for frame is leban’s wood (Vitex cotassus). It is reach 91,82 %. This indicates that the use of wood for frame is effective.Keywords:Tanjung Bakau, Frame, ship, wood.